Analisis Penerapan Model Pembelajaran Matematika di Kelas IV Sekolah Dasar Swasta Pelangi - Elvi Mailani; Anggina Hasanah Putri; Nabila Nasywa; Sakira Azzura Caniago; Ade Irma; Dea Febria Br Ketaren (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2026)
This study aims to determine the implementation of mathematics learning models in fourth-grade elementary school classrooms. The study was motivated by the continued use of the lecture method by teachers in the mathematics learning process. The use of the lecture method causes students to be less active, less confident, and less enthusiastic in participating in classroom learning activities. This research employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The findings revealed that teachers still predominantly use the lecture method because it is considered more practical and easier to implement. However, the use of this method makes the learning process monotonous, resulting in students becoming passive during lessons. In addition, the limited availability of learning media is one of the factors contributing to less engaging learning activities. Therefore, more innovative, creative, and interactive learning models are needed to encourage students to actively understand mathematical concepts. This study is expected to provide valuable input for teachers in improving the quality of mathematics learning in elementary schools.